Juridical Examination of Child Protection against Violence under Law Number 35 of 2014: A Case Study in Purwokerto, Indonesia - Mestika, Hana Fairuz; Mukarromah, Mufatikhatul; Hien, Thie Lay (The Digest: Journal of Jurisprudence and Legisprudence, 2022)
Diversity and Justice stand as norms within Indonesia's Criminal Justice System, as outlined in Law Number 11 of 2012 pertaining to the Juvenile Justice System. This legislation, inseparable from the UN Resolution concerning the Convention on Rights, ratified by the Government on January 26, 1990 through Presidential Decree Number 36 of 1990, finds its foundation in the Convention on the Rights of the Child. This study delves into the evolution of crimes against children in Indonesia. Firstly, it scrutinizes the imperative of safeguarding children in familial, educational, and broader societal contexts against violence and crime. Secondly, it assesses the effectiveness of the criminal justice system in providing protection for children as victims of violence and crime. Thirdly, it explores the state's responsibility in imposing sanctions through the criminal justice system. Employing a juridical-normative approach, this research relies on the collection of secondary data related to laws and regulations, drawing from materials in books, journals, and relevant sources. Observations reveal a distressing prevalence of children falling victim to violence, spanning beyond the confines of their homes to schools. Such violence encompasses not only physical harm but also psychological trauma. The onus of protecting, nurturing, and fostering the development of children lies with their environment, families, and schools. The efficacy of the juvenile justice system in combating crimes against children's rights hinges significantly on the functional application of criminal law.